Gamma-Aminobutyric Acid Increases the Production of Short-Chain Fatty Acids and Decreases pH Values in Mouse Colon - Xie, Min (Molecules, 2017)
Gamma-Aminobutyric acid (GABA) could regulate physiological functions in the gastrointestinal tract. The present study aimed to investigate the effect of GABA on colon health in mice. The female Kunming mice were given GABA at doses of 5, 10, 20 and 40 mg/kg/d for 14 days. Afterwards, the short-chain fatty acids (SCFAs) concentrations, pH values, colon index, colon length and weight of colonic and cecal contents were determined to evaluate the effects of GABA on colon health. The results showed that intake of GABA could increase the concentrations of acetate, propionate, butyrate and total SCFAs in colonic and cecal contents, as well as the weight of colonic and cecal contents. The colon index and length of the 40 mg/kg/d GABA-treated group were significantly higher than those of the control group (p < 0.05). In addition, decrease of pH values in colonic and cecal contents was also observed. These results suggest that GABA may improve colon health.